The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1956
DOI: 10.1084/jem.104.3.383
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resistance to Infection and Accompanying Alteration in Properdin Levels Following Administration of Bacterial Lipopolysaccharides

Abstract: The attention of immunologists has long been focused on acquired immunity produced by specific antigens. In the classical sense this type of immunity to infection, which generally is of a high order, depends upon the appearance of protective antibodies. The obvious importance of such artificial immunity, and the relative ease with which these antigens and antibodies could be studied, contributed to the comparative neglect of other components of bacterial cells which may also give rise to protective reactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
1

Year Published

1957
1957
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(62 citation statements)
references
References 13 publications
3
58
1
Order By: Relevance
“…Published data are conflicting as to the activity of the complement system in endotoxin tolerance (24,36). Since it is feasible that an increase in complement activity in the course of an acute-phase response elicited by endotoxin administration could account for improved phagocytosis in our model, we determined complement activity (50% hemolytic complement values) of sera from LPS-tolerant and control mice.…”
Section: Discussionmentioning
confidence: 99%
“…Published data are conflicting as to the activity of the complement system in endotoxin tolerance (24,36). Since it is feasible that an increase in complement activity in the course of an acute-phase response elicited by endotoxin administration could account for improved phagocytosis in our model, we determined complement activity (50% hemolytic complement values) of sera from LPS-tolerant and control mice.…”
Section: Discussionmentioning
confidence: 99%
“…with four additional 3-ml injections given each time to dogs and 0.5 ml to rabbits i.v. All animal challenge experiments were carried out more than 1 wk after completion of immunization to minimize "nonspecific" protective effects secondary to administration of lipopolysacchari(les (10,19,20).…”
Section: Animal Imamnizationsmentioning
confidence: 99%
“…As reviewed elsewhere, LPS initially gained interest as the component of gram negative bacteria responsible for toxicity and pyrogenicity, 3 but later studies revealed that it could generate protection from subsequent infection that correlated with increased antibody levels. [4][5][6] Findings that LPS-unresponsive mice are susceptible to gram-negative infections further highlighted the importance of this molecule in immune protection. 3 Therefore, a large body of research has been devoted towards investigating the adjuvant effects of LPS on lymphocytes.…”
Section: Introductionmentioning
confidence: 99%